Ibnu Rusyd's Brilliant Ideas in His Contribution to Islamic Education - Huda, Ali Anhar Syi'bul; Nurhuda, Abid; Putri, Anggi Ariska; Assajad, Anas (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Islam is very open to various fields of discipline so that it has experienced a period of glory in its time which is called the golden age of Islam. even many prominent scientists appeared at that time who contributed to the fields of philosophy, medicine to Islamic education, and one of the famous figures is ibnu rusyd. So the purpose of this study is to describe the brilliant ideas of Ibn Rushd in his contribution to Islamic education. The method used in this research is descriptive qualitative with a literature study model and then analyzed and concluded verificationally. The results showed that the fruit of his thoughts that contributed to the field of Islamic education, among others, did not need a separation between religious science and general science as his real efforts by uniting philosophy with sharia (religion). Then the classification of the level of understanding of students according to their development, and finally the birth of several methods and models in learning such as jadal, khitobi, and burhani learning methods. While in the aspect of the model, reasoning-based learning emerged such as PJBL, PBL, and demonstration.